THE SOCIOECONOMIC CONDITIONS OF ONLINE TAXI DRIVER FAMILIES DURING THE COVID-19 PANDEMIC IN JAKARTA GREATER AREA - Nurhasana, Renny; Matsuyuki, Mihoko; Hasan, Chotib; Shellasih, Ni Made; Ningtyas, Fadhilah Rizky; Fitrinitia, Irene; Negama, Toshiki; Kuwayama, Shoya (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
The Covid-19 pandemic affects almost all aspects of human life, from the education, transportation, political and economic sectors. Online taxi drivers are the informal sector that has been economically impacted by a decline in income. This study aims to determine the impact of the Covid-19 pandemic on the socio-economic aspects of the resilience of online taxi drivers since the implementation of Large-Scale Social Restrictions (LSSR) as regulated in Governor Special Capital Region Regulation of Jakarta No. 33/2020. The regulation made them experience a decrease in the number of passengers, thus affecting their income. This study uses a qualitative model with a case study design. Data collection was carried out by focus group discussions and in-depth interviews with a total of 4 informants obtained from purposive sampling, then analyzed using content analysis. They experienced a significant decrease in income of up to 60-70 percent per day, compared to before the pandemic. The decline in income and recommendations for social distancing affect the socio-economic aspects of family resilience from online taxi drivers as informal sectors. Therefore, they must look for other income alternatives. Therefore, they need various alternative jobs and assistance.